Learning Model And Motor Ability Towards Football Playing Skills In Sports High School Students - Ricky Fernando; Joni Alpen (STKIP Muhammadiyah Kuningan, 2023)
This study aims to determine: (1) the difference in the influence between the tactical learning model and the direct learning model on football playing skills in Riau provincial sports SMAN students, (2) the interaction between the learning model and motor ability on football playing skills in Riau provincial sports sman students (3) Differences in the influence of direct learning models on football playing skills on high ability motorcycles, (4) Differences in the influence of direct learning models on football playing skills on low motor ability. This type of research is an experiment using a factorial design of 2 x 2. The population in this study was 76 students who were active in the sport of football. The sample in this study was 20 people using a purposive random sampling technique followed by ordinal pairing to divide the group. The instruments in this study were football skills tests, (1) passing and stopping, (2) dribbling, (3) shooting, (4) heading, barrowmotor ability tests, (1) standing broad jump, (2) softball throws, (3) wall passes, (4) medicine ball puts, (5) 60 yards running using ANAVA two Away data analysis techniques. The results showed that: (1) there was a significant difference in influence between the tactical learning model and the direct learning model on improving football playing skills, (2) There was an interaction between the learning model and motor ability on football playing skills in students of sports high schools, (3) Tactical learning models and direct learning models in the group of high ability motor students on playing skills Football has the same result. (4) The tactical learning model provides more significant results than the direct learning model of football playing skills in students with low motor ability.